CORPORATE RAIDS AND SMALL BUSINESS - V. V. Dubyaga; Yu. O. Dubyaga (Russian Journal of Economics and Law, 2013)
The article discusses the forms and prerequisites of raiders’ captures. The features and trends of this phenomenon in Russia are analyzed. The existing counter measures against unwanted merges are viewed. A complex of measures for raiders’ problem solving is proposed.